(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There has been an increase in demand for free-form building through the development of advanced technologies, and the fourth industrial revolution has become a worldwide trend, thereby changing the construction industry. In particular, in the case of the free-form architecture sector, development of 3D printing technologies has been ongoing for construction automation. According to such trends, this study develops an FCP production equipment using 3D printing technologies. The FCP production equipment in this study is made up of mould equipment and 3D printer. It is different from existing 3D printing technologies so in this study 3D concrete extrusion nozzle must be developed for producing FCP. Basic design suitable to such requirements is proposed. Applicability of the proposed design is checked and the nozzle form is concretized to draft the final drawing. In this study, slit-type opening and closing device for accurate extrusion stoppage of concrete and screw-type nozzle for adjusting pressure and extrusion speed were applied for the nozzle. This is expected to be innovative technology for the FCP production sector.